Monoclonal antibodies define a domain on herpes simplex virus glycoprotein B involved in virus penetration. - Highlander, S L (1988)
In an earlier report (S.D. Marlin, S.L. Highlander, T.C. Holland, M. Levine, and J.C. Glorioso, J. Virol. 59: 142-153), we described the production and use of complement-dependent virus-neutralizing monoclonal antibodies (MAbs) and MAb-resistant (mar) mutants to identify five antigenic sites (I to V) on herpes simplex virus type 1 glycoprotein B (gB). In the present study, the mechanism of virus neutralization was determined for a MAb specific for site III (B4), the only site recognized by MAbs which exhibited complement-independent virus-neutralizing ability. This antibody had no detectable effect on virus attachment but neutralized viruses after adsorption to cell monolayers. These findings implied that the mechanism of B4 neutralization involved blocking of virus penetration. The remaining antibodies, which recognized sites I, II, and IV, required active complement for effective neutralization. These were further studied for their ability to impede virus infectivity in the absence of complement. Antibodies to sites I (B1 and B3) and IV (B6) slowed the rate at which viruses penetrated cell surfaces, supporting the conclusion that antibody binding to gB can inhibit penetration by a virus. The data suggest that MAbs can interfere with penetration by a virus by binding to a domain within gB which is involved in this process. In another assay of virus infection, MAb B6 significantly reduced plaque development, indicating that antibody binding to gB expressed on infected-cell surfaces can also interfere with the ability of a virus to spread from cell to cell. In contrast to these results, antibodies to site II (B2 and B5) had no effect on virus infectivity; this suggests that they recognized structures which do not play a direct role in the infectious process. To localize regions of gB involved in these phenomena, antibody-binding sites were operationally mapped by radioimmunoprecipitation of a panel of truncated gB molecules produced in transient-expression assays. Residues critical to recognition by antibodies which affect penetration by a virus (sites I, III, and IV) mapped to a region of the molecule (amino acid residues 241 to 441) which is centrally located within the external domain. Antibodies which had no effect on penetration (site II) recognized sequences distal to this region (residues 596 to 737) near the transmembrane domain. The data suggest that these gB-specific MAbs recognize two major antigenic sites which reside in physically distinct components of the external domain of gB.(ABSTRACT TRUNCATED AT 400 WORDS)